(untitled) (Journal of Imam Al-Kadhim College, 2023)
Apstract: The research talked about one of the prominent stylistic features in recent studies, which is displacement Definition of displacement phenomena and their divisions. Displacement in the language: (it is the disappearance of something and its removal, and it is said that the thing is removed, it is removed, if it is gone) As for in idiomatically, it is a departure from the usual or what the apparent necessitates, or it is a departure from the standard for a purpose intended by the speaker, or it came with the will of the mind, but it serves the text in one way or another and to varying degrees. It is the poet’s artistic ability to form relationships between expressions to create creative horizons for texts, and among the manifestations of displacement that the research examined in the study: manifestations of semantic displacement from metaphor and analogy) and manifestations of synthetic displacement from introduction and delay - deletion, turning around, and bringing poetic evidence to them. A poet with a long history in the field of poetry, Khasab al-Qariha, was distinguished by his linguistic purchase, from which he draws from the extent that opened his poetic horizons, and his cultural and literary stock resulting from his environment that provided him with the heritage and cultural background, in addition to his fondness for reading and reading literature books and Arabic collections.